2023
DOI: 10.1186/s12879-023-08165-4
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality and associated factors among people living with HIV initiating highly active antiretroviral therapy in Luzhou, China 2006–2020

Abstract: Background To estimate crude mortality, excess mortality, and standardized mortality rates (SMR) among people living with HIV (PLHIV) initiating highly active antiretroviral therapy (HAART) in Luzhou, China 2006–2020, and assess associated factors. Methods PLHIV initiating HAART in the HIV/AIDS Comprehensive Response Information Management System (CRIMS) in Luzhou, China 2006–2020 were included in the retrospective cohort study. The crude mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The results of the survival analysis demonstrated that the greatest number of deaths occurred within the first year of ART initiation, with 29.49% (146/495) of the total mortality attributed to AIDS-related illnesses. These findings are consistent with previous studies ( 9–11 , 13 , 14 ), emphasizing the critical and high-risk nature of the initial treatment year and the importance of enhanced follow-up and monitoring for newly treated patients, improved treatment adherence, and support for immune system reconstruction. The cumulative survival rates for patients at 1, 5, 10, and 15 years after ART initiation were 0.97, 0.90, 0.85, and 0.79 ( Table 2 ), respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the survival analysis demonstrated that the greatest number of deaths occurred within the first year of ART initiation, with 29.49% (146/495) of the total mortality attributed to AIDS-related illnesses. These findings are consistent with previous studies ( 9–11 , 13 , 14 ), emphasizing the critical and high-risk nature of the initial treatment year and the importance of enhanced follow-up and monitoring for newly treated patients, improved treatment adherence, and support for immune system reconstruction. The cumulative survival rates for patients at 1, 5, 10, and 15 years after ART initiation were 0.97, 0.90, 0.85, and 0.79 ( Table 2 ), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Heterosexual transmission was identified as the predominant mode of HIV infection in this region, accounting for 93.97% of all transmission routes, whereas homosexual transmission only accounted for 2.61%, which is consistent with the findings from similar studies conducted in southwestern China, such as Liangshan, Sichuan Province (9), and Luzhou, Sichuan Province (13). However, in the eastern regions of China, including Nanjing City (10), Beijing City (11), and Tianjin City ( 14), the proportion of homosexual transmission exceeds that of heterosexual transmission.…”
Section: Discussionsupporting
confidence: 90%
“…A retrospective cohort study conducted in China between 2006 and 2020 demonstrated that the early initiation of ART in people living with HIV significantly reduced the mortality rate in this population, directly impacting overall mortality rates. However, the same study found that factors such as being male, having a very late HIV diagnosis, initiating ART after 12 months of diagnosis, and virologic failure (detectable viral load after 6 months of treatment initiation or modification) led to a higher mortality rate [ 29 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ayub et al, carbon nanocone oxide (ONC) is used as a drug carrier for zidovudine (ZVD) since they are efficient in delivering to the target site while reducing toxicity and generic accumulation, which are oen related with intravenous traditional methods. 23,25 Another promising avenue involves the use of nanoparticles, which offer precise drug targeting and reduce the need for frequent dosages. Nanoparticles encapsulate the drugs and deliver them directly to the specic target site within the body due to their diminutive size and polymeric composition.…”
Section: Introductionmentioning
confidence: 99%